Inguinal Hernia Repair on Day Care Basis During Global COVID-19 Pandemic - Syed Fahd Shah, Zahid Mehmood Minhas, Malik Jawad Faisal, Syed Hussain Shah, Syed Zubair Shah (Journal of Rawalpindi Medical College, 2021)
Abstract Background: COVID-19 has effected General Surgical Elective list and most of the surgical procedures are postpone. Inguinal hernia surgery can be performed under local anesthesia on day care basis in selected group of patients taking all necessary precautions for COVID-19. Patients & Methods: This prospective study was conducted at department of General Surgery Federal Hospital, Islamabad for a period of three months from 15th March 2020 to 15th June 2020. All patients were included in the study through purposive sampling and preference was given to patients elder than 50 years of age. This study included 59 adult patients with inguinal hernia who under mesh repair under local anaesthesia on day care basis. Results: A total of 59 patients were included in the study. All patients were male. The age range was from 37 to 82 years (SD=± 10.23). 30 (50.84%) patient had inguinal hernia on left side while 26 (44.06%) had hernia on right side. Mean Operative time was 35 min. Pain was chief complaint postoperatively 30 (50.8%) patients had moderate pain while 6 (10.1%) patients had severe pain in first 24 hours after surgery. Fever was present in 15 (25.42%) patients in first 24 hours. All patients were negative for COVID -19 preoperatively and after 2 weeks none of the patients develop any symptoms of COVID-19. 3 (5.08%) patients needed readmission within 24 hours for pain and some haemorrhage. There was no mortality in our study Conclusions: Inguinal Hernia Surgery under local anaesthesia on day care basis in a very good practice at this time of global pandemic of COVID-19. This is a safe and reliable strategy. Key words: Inguinal Hernia, COVID-19, Local Anaesthesia